Economic and legal impacts of delayed containers - Marta K. Kołacz; Katrien Storms; Christa Sys; Wouter Verheyen (Journal of Shipping and Trade)
Abstract Usage of containers beyond the predetermined period results in container demurrage and detention (D&D) that is charged by the carriers. The D&D charges are often perceived as a profit-making revenue stream for carriers, which raises the question of whether D&D charges adequately balance the ecosystem actor's interests. D&D charges in the maritime ecosystem have not received wider attention, the focus so far being mainly on some operational aspects of container delays. This paper contributes to the literature by mapping the ecosystem members' interests and proposing how to make these interests more balanced as far as D&D charges are concerned. For that purpose, economic (cost analysis) and legal (doctrinal and comparative) perspectives are employed. The conducted analysis presents the carrier’s opportunity costs and confirms that there might be a notion of the profit-making nature of D&D, which is not sufficiently mitigated under the existing legal framework. The legal framework provides mainly ex-ante mitigation strategies for which a party burdened with a D&D invoice would need to file a court claim. Nevertheless, the correction standards to prevent exaggerated D&D charges are largely missing. The paper suggests contractual and regulatory solutions that could help balance the ecosystem actors’ interests as far as D&D charges are concerned.